2019
DOI: 10.1177/0300891619871344
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropulmonary blastoma: a report from the TREP (Tumori Rari in Età Pediatrica) Project

Abstract: Introduction: Pleuropulmonary blastoma (PPB) is a rare, aggressive mesenchymal tumor of childhood. The Italian Tumori Rari in Età Pediatrica (TREP) Registry was the first in Europe dedicated to prospective data collection on rare pediatric tumors. We analyzed data from an Italian series of patients with PPB, focusing on the role of the TREP Project. Methods: We considered patients aged 0–14 with histologically confirmed diagnosis, registered in population-based cancer registries (before 2000) or the TREP Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Surgery represents the mainstay of treatment, to establish the diagnosis and cure the patient. Although limited by number of patients, published reports have shown that complete tumour resection is a major prognostic factor [ 3 , 9 12 ].…”
Section: Perioperative Managementmentioning
confidence: 99%
“…Surgery represents the mainstay of treatment, to establish the diagnosis and cure the patient. Although limited by number of patients, published reports have shown that complete tumour resection is a major prognostic factor [ 3 , 9 12 ].…”
Section: Perioperative Managementmentioning
confidence: 99%
“…Type I PPB is a localized tumor, but Types II or III PPB may be associated with metastasis at diagnosis, during treatment, or after completion of therapy. The most common metastatic sites are within the thorax or CNS although bone, liver, and lymph nodes may also be involved 17,22 …”
Section: Recommendationsmentioning
confidence: 99%
“…A surgical procedure is necessary to obtain a tumor sample and establish the diagnosis of PPB. Different series, although with a limited number of patients, have shown that complete tumor resection is a major prognostic factor 16,17,22–24 . Therefore, surgery is fundamental for the diagnosis and treatment in children with PPB (Level IV, Grade A).…”
Section: Recommendationsmentioning
confidence: 99%
“…(5-year overall survival 53-71%). 20,54 In our analysis, mean age at diagnosis of 3.1 years was observed for these patients, indicating a higher proportion of type-II-and type-III-PPB. Most children with PPB have a heterozygous DICER1 germline variant, but this mutation has no prognostic impact.…”
Section: Discussionmentioning
confidence: 54%
“…PPBs are of mesenchymal origin with primitive embryonal‐like blastema and stroma and are classified into three distinct types depending on the mixture of cystic and solid components 1,53 . While type I‐PPB has a higher cystic component and a younger mean age of 8 months at diagnosis that results in a more favorable outcome (5‐year overall survival, 86%–91%), type‐II‐PPB and type‐III‐PPB occur in older children (35 months and 41 months, respectively), have more solid tumor components and are associated with a worse outcome despite the addition of chemotherapy to surgical treatment options (5‐year overall survival 53–71%) 20,54 . In our analysis, mean age at diagnosis of 3.1 years was observed for these patients, indicating a higher proportion of type‐II‐ and type‐III‐PPB.…”
Section: Discussionmentioning
confidence: 99%